The Utilization of Religious Content in Social Media for the Alteration Adolescent’s Islamic Behaviour - Muhammad Luthfi; Syukur Kholil; Lahmuddin Lubis; Ahmad Tamrin Sikumbang (Dialogia, 2022)
The exposure of social media has also changed the pattern of acceptance of da’wah, especially changes in accessing religious content and changes in the religious behavior of adolescents.  This article analyzes the use of religious content on social media in changing the Islamic behavior of adolescents at the Al Jihad Mosque in Medan. The type of research used is a qualitative approach using descriptive methods. The data collection technique used is a direct interview method to adolescents at the Al Jihad Mosque in Medan. The result of this study is theuse of religious content on social media through video lectures on YouTube to facilitate the understanding of Islamic adolescents at the Al Jihad Mosque in Medan. Meanwhile, the obstacle to the use of religious content on social media in changing the Islamic behavior of adolescents is that da'i cannot know the characteristics of mad'u.  The results that can be achieved are the improvement of personal behavioral values, such as tauhid, worship, and morals in living their lives.